Adaptive tuning of PID using chef‑based optimization algorithm for improving automatic voltage regulator - Widi Aribowo; Reza Rahmadian; Mahendra Widyartono (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
This  article  presents  the  proportional-integral-derivative  (PID)  parameter tuning  on  the  automatic  voltage  regulator  (AVR)  using  the chef-based optimization   algorithm   (CBOA).   CBOA   is   modeling   cooking   training activities consisting of students and young chefs in an effort to mature cooking skills.  This  article  uses  other  methods  as  a  comparison  in  measuring  the performance  of  the  proposed  method.  The  methods  used  are grasshopper optimization algorithm (GOA) and cooperation search algorithm (CSA). The simulation results show that the proposed method, namely CBOA, has a better ability in the peak value of overshoot, which is 0.232% compared to the CSA method and 12.99% compared to the GOA method.